Efficacy of pre-insemination treatment with GnRH for improving conception rate in repeat breeder cows - SHELAR, R R; DEOPURKAR, V L; BAKSHI, S A; GULAWANE, S U (The Indian Journal of Animal Reproduction, 2023)
An attempt was made to asses pre-insemination use of Gonadotropin Releasing Hormone (GnRH) in 20 noninfectious repeat breeding Gir Cows and its crossbreds (G x HF, G x J ). Buserline 10 ug was injected intramuscularly just before insemination in treatment group of animals. Conception rate in the treatment group was 20% higher than the control. GnRH had no influence on subsequent serum progesterone level on 14th and . 22nd day post-insemination. The properties of estrual mucus discharge (pH, Spinnbarlceit test and in-vitro sperm penetration test) differed significantly between fertile and nonfertile estrus.